Artificial limbs, etc. for Spanish refugees : memorandum of interview with Walter Schevenels and George Jeger on 25 Jan 1940 - Morgan, H. B. (Hyacinth Bernard Wenceslaus Morgan), 1885-1956
1940-01-29 042-0020-002 292/946/42/20(ii)